Pengembangan Virtual-Lab Berbasis STEM Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Rona Taula Sari*; Siska Angreni; Feni Julia Salsa (Jurnal Pendidikan Sains Indonesia, 2022)
Innovative and creative learning media are needed to overcome online practicum during the pandemic to improve students' critical thinking skills, namely the development of STEM-Based Virtual-lab media. The purpose of this research is to produce a STEM-based Virtual-Lab media to improve students' critical thinking skills that are valid, practical and effective. The development model used is 4-D development which consists of define, design, develop and disseminate. However, in this study only the development stage was carried out. The research instrument was a validity questionnaire that was assessed by media, material and language experts, a product usability practicality questionnaire by students and a critical thinking ability test for 30 PGSD students at Bung Hatta University. Sampling was carried out non-probability with purposive sampling technique. The level of understanding of students' concepts was analyzed by ngain. The results of the study stated that the virtual lab media produced for students of the Bung Hatta University Elementary School Teacher Education study program was declared valid by material, language and design experts. Based on the trial implementation of the Virtual Lab media, it is in the very practical category. Assessment of student learning outcomes shows that completeness exceeds the minimum limit for calculating ngain at 0.66 with moderate criteria. Therefore, the virtual laboratory media developed for students of the STEM-based primary school teacher education study program was declared effective. Thus, it can be concluded that STEM-based Virtual-Lab media is produced to improve students' critical thinking skills that are valid, practical and effective